2010
DOI: 10.4155/bio.10.91
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of DBS Within Drug Discovery: Development of a Serial Microsampling Pharmacokinetic Study in Mice

Abstract: Serial microsampling and DBS in exploratory mouse pharmacokinetic has been shown to provide superior data quality when compared with traditional plasma-based composite studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…Clark et al [17]. showed that FTA Elute papers produced the most marked matrix effects and therefore comparisons were made using S&S 903 filter paper.…”
Section: Matrix Effectmentioning
confidence: 99%
“…Clark et al [17]. showed that FTA Elute papers produced the most marked matrix effects and therefore comparisons were made using S&S 903 filter paper.…”
Section: Matrix Effectmentioning
confidence: 99%
“… DBS environmental conditions during ambient shipping and storage across international borders (49) .  DBS sample homogeneity (50,51,52,21) .…”
Section: Recent Investigations Into Fundamentals Principles Associatementioning
confidence: 99%
“…Tail vein sampling (tail clip and tail vein with needle hub) seems to be the most commonly used micro-sampling technique in mice (2,12,30,31) while saphenous bleeds and retroorbital bleeds have also been used (3,4,12). The use of tail clips and tail vein with a hub needle should be avoided to reduce contamination of samples with administered dose, especially in small rodents such as mice when drug/test compounds are administered IV via the tail vein.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the adoption of various bleeding techniques to enable micro-sampling of blood or plasma (generally defined as the collection of blood volumes of less than 50 µL) has enabled the collection of multiple PK time points and the generation of a complete PK profile from a single mouse. These techniques include micro-sampling of plasma either as liquid plasma (8)(9)(10), or as dried plasma spots (11), and micro-sampling of blood either as liquid blood (12)(13)(14)(15), or as dried blood spots (DBS) (2)(3)(4)(16)(17)(18). Overall, micro-sampling also benefits the adoption and compliance with the 3Rs principles (Reduction, Refinement, and Replacement in animal usage) (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation